Laemophloeus souzalimai, a new species of lined flat bark beetle (Coleoptera, Cucujoidea, Laemophloeidae) from Southeast Brazil - Bento, Matheus (Zootaxa, 2021)
Distinctive, remarkable specimens from Bauru, São Paulo state, Brazil are recognized as a new species of the genus Laemophloeus Dejean (sensu stricto), which is described and illustrated in this paper. Laemophloeus souzalimai sp. nov. is most similar to L. germaini Grouvelle and can be readily distinguished from all New World species of the genus by the dorsal color testaceous, without elytral maculae, antennal club of 6 antennomeres, genal processes anteriorly projected, male head with somewhat pedunculated eyes, and frons with a broad, V-shaped impressed line. Additionally, the preexisting key to Laemophloeus species with antennal club of 6 or more antennomeres is modified to include the new species, and new records for five Brazilian species of the genus are provided.